Development Of External Beam Therapy 3 Ultraviolet Dosimeter - Ahmad Shah, Wan Insaniah Saleha (2018)
Solar ultraviolet radiation is well known to potentially brings harmful effect to human health when exposed in a prolong nature. Hence, the routine measurement of exposed solar ultraviolet (UV) dose is essential. The existing method in determining solar UV exposure is through UV meter. The problem found in this method is that it can only allow a single point measurement (i.e, an instantaneous UV intensity) in mW/cm². This means it does not record accumulative UV dose at one time. So, for this instrument to operate, it requires continuous exposure to outdoor environment which may cause defect to the instrument due to overheating.